2021
DOI: 10.3390/nu13020428
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Processed Food Consumption is Associated with Renal Function Decline in Older Adults: A Prospective Cohort Study

Abstract: Ultra-processed food (UPF) consumption has been associated with increased risk of cardiovascular risk factors and mortality. However, little is known on the UPF effect on renal function. The aim of this study is to assess prospectively the association between consumption of UPF and renal function decline. This is a prospective cohort study of 1312 community-dwelling individuals aged 60 and older recruited during 2008–2010 and followed up to December 2015. At baseline, a validated dietary history was obtained. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 70 publications
1
24
0
1
Order By: Relevance
“…The main and novel finding is that participants consuming a higher proportion of UPFs in their diets were at higher risk of worse kidney outcomes in the general population. Our findings are in agreement with a recent, small-scale study showing that high UPF consumption is independently associated with an increase in the risk of kidney function decline in Spanish older adults ( 32 ). We are not aware of other studies evaluating this in the overall general population, but our results expand previous research linking UPF consumption with risks of other noncommunicable diseases, such as cardiovascular disease ( 24 ) and diabetes ( 25 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The main and novel finding is that participants consuming a higher proportion of UPFs in their diets were at higher risk of worse kidney outcomes in the general population. Our findings are in agreement with a recent, small-scale study showing that high UPF consumption is independently associated with an increase in the risk of kidney function decline in Spanish older adults ( 32 ). We are not aware of other studies evaluating this in the overall general population, but our results expand previous research linking UPF consumption with risks of other noncommunicable diseases, such as cardiovascular disease ( 24 ) and diabetes ( 25 ).…”
Section: Discussionsupporting
confidence: 93%
“…The interaction by cardiovascular disease history was only significant for the annual change in the eGFR endpoint ( Figure 2 ). A prior study focusing on the relationship between UPF consumption and kidney function declines in elderly individuals found no consistent interaction by several cardiovascular risk factors (hypertension, diabetes, and obesity) ( 32 ). Other studies focusing on other dietary exposures in relation to kidney function found similar results.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other dietary adjustments include for fried foods, fruit and vegetables, UPF soft drinks, multivitamin use and excluding bacon, sausage and processed meats from ultra-processed food intake. These adjustments had no impact on the association between higher intakes of UPF and risk of all-cause mortality, cancer, overweight/obesity, increased total and visceral fat mass, increased BMI and FMI, NAFLD, weight and waist circumference gain, adverse blood lipid profiles, grip strength decline, incident hypertension and renal function decline [ 103 , 104 , 106 , 107 , 109 , 111 , 112 , 115 , 121 , 122 , 125 , 126 , 133 , 136 , 138 ].…”
Section: Review Of Prospective Studies Adjusting For Dietary Qualitymentioning
confidence: 99%
“…Healthy dietary patterns, based on fresh products and rich in fruits, vegetables and dietary fiber are inversely associated with kidney function decline [7], CKD [8], and CKD mortality [9]. On the contrary, Westernized diets, high in energy, saturated fat, sugar, salt, and ultra-processed foods, have been associated with higher mortality [10,11], several chronic diseases including CVD [12,13], and kidney function decline [14].…”
Section: Introductionmentioning
confidence: 99%